Peran Pembelajaran Quantum Learning dalam Meningkatkan Literasi Siswa di Kelas - Dewi Insyiroh; Yesha Tri Anita Utami; Agus Milu Susetyo (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
TANDUR type quantum learning aims to make mathematics more interactive and fun to learn. The main goal of this model is to increase students' desire to learn, improve their writing skills, and create effective communication between teachers and students. Through systematic processes such as Grow, Experience, Name, Demonstrate, Repeat, and Celebrate, students learn about things related to everyday life. Additionally, this approach creates a dynamic learning environment, encourages active participation, and enables meaningful learning. Through a structured and experience-based approach, the TANDUR type quantum learning model is expected to continuously improve students' literacy and writing skills.